2014
DOI: 10.3389/fncir.2014.00066
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of gap junctions at glutamatergic mixed synapses in adult Mosquitofish spinal cord neurons

Abstract: “Dye-coupling”, whole-mount immunohistochemistry for gap junction channel protein connexin 35 (Cx35), and freeze-fracture replica immunogold labeling (FRIL) reveal an abundance of electrical synapses/gap junctions at glutamatergic mixed synapses in the 14th spinal segment that innervates the adult male gonopodium of Western Mosquitofish, Gambusia affinis (Mosquitofish). To study gap junctions’ role in fast motor behavior, we used a minimally-invasive neural-tract-tracing technique to introduce gap junction-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…We feel that the most likely explanation for the lack of effect on gravitaxis by glutamate receptor antagonists at 25 hpf is that the antenna cell to antRN synapses have transitioned to being predominantly electrical. The 21-hpf connectome shows an abundance of putative gap junctions between the antenna cells and antRNs, much more than was observed between the photoreceptors and their relay neurons ( Figure S1) [21], and mixed electrical/glutamatergic synapses appear to be common [41]. However, we found that continuous exposure to perampanel from 21 to 25 hpf did not reduce the gravitaxis response at 25 hpf, indicating that, if there is a transition from chemical to electrical synapse, one does not depend on the other (data not shown).…”
Section: Glutamatergic Responses At 21 and 25 Hpfmentioning
confidence: 93%
“…We feel that the most likely explanation for the lack of effect on gravitaxis by glutamate receptor antagonists at 25 hpf is that the antenna cell to antRN synapses have transitioned to being predominantly electrical. The 21-hpf connectome shows an abundance of putative gap junctions between the antenna cells and antRNs, much more than was observed between the photoreceptors and their relay neurons ( Figure S1) [21], and mixed electrical/glutamatergic synapses appear to be common [41]. However, we found that continuous exposure to perampanel from 21 to 25 hpf did not reduce the gravitaxis response at 25 hpf, indicating that, if there is a transition from chemical to electrical synapse, one does not depend on the other (data not shown).…”
Section: Glutamatergic Responses At 21 and 25 Hpfmentioning
confidence: 93%
“…RNA sequencing of zebrafish larvae exposed to PCB153 in a similar exposure regime (4-120 hpf) and concentration (10 µM) significantly altered the expression of connexin genes cx28.9, cx42, and cx35b (Aluru et al 2020). Cx35 is expressed on the Mauthner neuron lateral dendrites in zebrafish (Jain et al 2018) and plays a crucial role in regulating spinal motor activity during fast motor behavior of adult mosquitofish (Serrano-Velez et al 2014). We thus propose that gap junction function could be disrupted, which may be a future study direction using single-cell RNA sequencing or genetically encoded optogenetics that has yet to be developed in a model organism (Dong et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The novel region includes a highly modified anal fin used for sperm transfer (the gonopodium) along with its musculoskeletal components. This unique region comprises vertebrae with ribs and hemal spines (Rosa-Molinar et al, 1994 and is thought to reflect an adaptation for rapid and effective sperm transfer and internal fertilization in the group (Rivera-Rivera et al, 2010;Serrano-Velez et al, 2014). The ano-urogenital region is situated between the anterior trunk and posterior caudal regions, from vertebrae 11 to 16.…”
Section: Introductionmentioning
confidence: 99%